Contractual obligations analysis for construction waste management in Canada - Mendis, Daylath; Hewage, Kasun N.; Wrzesniewski, Joanna (Journal of Civil Engineering and Management, 2015)
Construction industry creates a massive amount of waste, which typically ends up in landfills. Canadian construction industry represents 30% of the total municipal solid waste deposited in landfills. Construction and demolition (C&D) waste has created negative socioeconomic and environmental impacts including contaminating ground water, emitting greenhouse gases, and adding more waste to scarce landfills. Literature is cited rework/waste generation due to ambiguity/errors in construction contract documents. Exculpatory clauses in contract documents are included in contractual agreements to prevent contractor claims, which often cause rework. After an extensive contract documents review, these clauses were categorized in to eight major areas. This paper (1) analyses expert opinions on pre-identified contractual clauses; and (2) introduces recommendations to minimize rework and waste in construction projects. It was found that the clauses related to quality, workmanship, and field quality control/inspection have the most potential to generate construction waste.